Precise pathologic diagnosis and individualized treatment improve the outcomes of invasive micropapillary carcinoma of the breast: a 12-year prospective clinical study. (June 2018) - Li, Weidong; Han, Yunwei; Wang, Chijuan; Guo, Xiaojing; Shen, Beibei; Liu, Fangfang; Jiang, Chengying; Li, Yaqing; Yang, Yiling; Lang, Ronggang; Fan, Yu; Gu, Feng; et al.
Abstract Invasive micropapillary carcinoma of the breast is a histologic subtype of breast cancer and associated with high incidence of lymphovascular invasion, lymph node metastasis and poor prognosis. The aim of this prospective study was to investigate the impact of precise pathologic diagnosis and individualized treatment on the outcomes of invasive micropapillary carcinoma of the breast. The study group included 2299 women with invasive micropapillary carcinoma diagnosed at Tianjin Medical University Cancer Institute and Hospital between January 2004 and December 2015. In the study group, specimens were examined with the method of whole-specimen orientation and serial sectioning, and patients received precise pathological diagnosis and individualized treatment. The control group of invasive micropapillary carcinoma consisted of 163 cases, identified through a retrospectively review of 9056 invasive carcinomas diagnosed at our institution between January 1989 and December 2003 using the standard pathology-evaluation method (i.e., not using the whole-specimen orientation and serial-sectioning method). The clinicopathological features, treatments and outcomes were compared between the two groups. The incidence of invasive micropapillary carcinoma in the study group was 6% (2299/39, 714 cases), significantly higher than that of the control group (2%; 163/9056 cases). The 5-year disease-free survival in the study group was significantly higher than that in the control group (83.8 vs.45.4%;p  < 0.05). The 5-year overall survival was significantly increased from 57.4% in the control group to 90.9% in the study group (p  < 0.05). In the multivariate analysis, lymphovascular invasion, estrogen receptor status and lymph node metastasis were independent prognostic factors. Although invasive micropapillary carcinoma of the breast is associated with poor prognosis, precise pathologic diagnosis and individualized treatment improved the disease-free survival and overall survival of invasive micropapillary carcinoma patients. Precise pathological diagnosis is the premises for individualized treatments and for improving the outcomes of patients with invasive micropapillary carcinoma of the breast.